Comparative Analysis of Process Innovation Strategies: A Study of Family and Non-Family Indian IT Firms - Phani K. R.; Kumar Mukul (Qubahan Academic Journal)
This conceptual paper delves into the dynamic realm of process innovation within the Indian Information Technology (IT) sector, scrutinizing the unique strategies and methodologies adopted by both family and non-family-owned firms. Employing a comprehensive analysis, we aim to uncover distinct approaches employed by these entities to drive and effectively implement process innovation. This paper contributes valuable insights into the intricate interplay of familial structures and corporate innovation, shedding light on how these factors shape the trajectory of technological advancements in the Indian IT landscape.